INCREASING TEACHERS' ABILITY TO APPLY LEARNING MEDIA THROUGH IN HOUSE TRAINING - Arip, M. (Jurnal Kajian Pembelajaran dan Keilmuan, 2021)
AbstractLearning media is an important factor in improving the quality of learning. This is due to the development of technology in the field of education that demands efficiency and effectiveness in learning. This study aims to determine the role of In House Training (IHT) activities in improving the ability of teachers to apply learning media at SMP Negeri 5 Sungai Kakap. This study uses two cycles of action research. Each cycle consists of four stages, namely: design, activities and observations, reflection and revision. The target of this research is the teachers of SMP Negeri 5 Sungai Kakap. The obtained data is the result of cyclical actions during the School Action Research (PTS) activity. Based on the research that has been done, it can be concluded that the implementation of has a positive impact in improving the ability of teachers to apply learning media. This is indicated by the increase in the acquisition score made by the teacher in each cycle from the results of the actions taken which are proven to increase the ability of teachers to apply learning media, namely the assessment of teacher activities when participating IHT activities from 21, in cycle 1 it increased to 25. .57 in cycle 2. Then the assessment of the teacher's ability to apply learning media also increased. Before the IHT activity was held, the average score of teachers in applying learning media was only 58.57%, while in cycle 1 the average score was 71 ,42% increased to 82.85% in cycle 2.Â Keywords: In House Training, Learning Media, Teacher Ability